STUDY OF CHROMATOGRAPHIC FINGERPRINT OF FLAVONOID COMPOUNDS OF THE BUR-MARIGOLD HERB - ELINA E. KOTOVA; SEMEN A. KOTOV; ANDRIY G. KOTOV (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The main aim of this work was to determine the possibility of reliable identification of phenolic compounds, in particular flavonoids, specific for very popular type of medicinal plant material Bidens (B. tripartita, B. frondosa, B. cernua), their qualitative and quantitative determination by various methods: TLC, HPLC and absorption spectrophotometry (UV method). TLC method was used to isolate a specific compound from B. cernua sample, and by using HPLC method this compound was identified as quercitrin in comparison with a reference sample. A study of 8 series of the bur-marigold herb has shown that the presence of significant amounts of quercitrin in the sample indicates an unacceptable impurity of B. cernua in the pharmacopeial samples of B. tripartita. The main components of B. tripartita were identified as: luteolin-7-glucoside, unidentified luteolin glycoside, luteolin, derivatives of caffeic acid, in particular chlorogenic acid, polyacetylenes, chalcones. The correlation between the results of quantitative determination of the sum of flavonoids by the UV method and the results of HPLC determination of main components was shown.